2007
DOI: 10.1007/s10750-007-9076-3
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Daphnia lacustris G.O. Sars, 1862 (Crustacea, Anomopoda): a cryptic species in the Daphnia longispina group

Abstract: While molecular markers have revealed several distinct species within the Daphnia longispina group, there is a need to reconcile these species with traditional nomenclature. Here we show that one such species, called D. longispina in recent literature based on molecular markers, can reliably be associated with the described taxon Daphnia lacustris G.O. Sars, 1862. Both mitochondrial and nuclear molecular markers readily distinguish this species from others in the D. longispina group. D. lacustris is absent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 25 publications
3
35
0
Order By: Relevance
“…Our observation that cryptic taxa may be associated with differences in depth and habitat permanence is in line with other work. Schwenk et al (2004) showed that depth associated with other factors was an important ecological variable to explain the separation of Daphnia umbra and D. longispina, later considered as Daphnia lacustris (Nilssen et al 2007), with the former species occurring in larger and deeper waterbodies and the latter occurring in shallow ponds.…”
Section: Environmental Factors Structuring Genetic Variation In Moinamentioning
confidence: 99%
“…Our observation that cryptic taxa may be associated with differences in depth and habitat permanence is in line with other work. Schwenk et al (2004) showed that depth associated with other factors was an important ecological variable to explain the separation of Daphnia umbra and D. longispina, later considered as Daphnia lacustris (Nilssen et al 2007), with the former species occurring in larger and deeper waterbodies and the latter occurring in shallow ponds.…”
Section: Environmental Factors Structuring Genetic Variation In Moinamentioning
confidence: 99%
“…Members of this genus have long been used as model organisms in various fields of basic and applied science, from aquatic ecology and evolutionary biology to ecotoxicology; however, their taxonomy is far from resolved. Many undescribed cryptic species are still being discovered (see, e.g., Adamowicz et al, 2009), and discussions about the status and validity of even very common Daphnia species remain controversial (e.g., Nilssen et al, 2007;Petrusek et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, new cladoceran species have been recognized as deep morphological and genetic comparisons between populations from different regions were conducted (e.g. De Melo and Hebert, 1994; Kappes and Sinsch, 2002;Nilssen et al, 2007;Elías-Gutiérrez and Valdez-Moreno, 2008;Belyaeva and Taylor, 2009;Kotov et al, 2009;Sinev and Elmoor-Loureiro, 2010;Van Damme et al, 2011). Therefore, B. huaronensis populations should be compared in their morphology, genetics and ecology in order to access their taxonomic status.…”
Section: Discussionmentioning
confidence: 99%